Intelligent power sharing of DC isolated microgrid based on fuzzy sliding mode droop control - Mi, Yang (2020)
Linear droop control can realize power sharing among generators in dc microgrid (MG) without relying on critical communication links. However, the droop relationship between output power and voltage magnitude of renewable power generate system is nonlinear with uncertainties and disturbances from renewable sources and loads in practical dc MG. A novel droop scheme is proposed for an isolated dc MG to solve the nonlinear problem. The control strategy is proposed by using the Takagi-Sugeno (T-S) fuzzy model and sliding mode algorithm. The nonlinear droop characteristics can be represented by T-S model through taking advantage of locally measured output variables. The sliding mode droop controller is designed for compensating the uncertainties and disturbances to derive accurate power sharing based on T-S fuzzy model. The proposed scheme is proved to be effective under variable operating conditions through PSIM/MATLAB simulation.